The Effect of the PBL Model on Critical Thinking Ability and Mathematics Learning Achievement of Class V Students of SDN Anggrek Cluster - Usman; Mery Noviyanti; Erwin (South Sulawesi Education Development (SSED), 2024)
This study aims to determine the Effect of the application of the PBL model on critical thinking skills and mathematics learning achievement and determine the influence of learning achievement and critical thinking of students using conventional learning. The research method uses experimental quasi. The study population was 159 learners, with a research sample of 22 learners. The instruments used are educator activity observation sheets, student activity observation sheets, questionnaires on applying PBL models, critical thinking ability tests, and learning achievement tests. Data analysis using the T-test. The results of the first hypothesis obtained by Sig. (2-tailed) were 0.00 ≤ 0.05, the average value of applying the experimental class PBL model was 78.23, the standard deviation was 11.936, the average control class was 5.025, the standard deviation was 5.025, and Sig obtained the second hypothesis. (2-tailed) was 0.00 ≤ 0.05, the average value of critical thinking of the experimental class was 82.95, the standard deviation was 13.062, and the average critical thinking of the control class was 58.00, the standard deviation was 11.940, the third hypothesis obtained by Sig. (2-tailed) is 0.00 ≤ 0.05, the average value of experimental class learning achievement is 83.64, the standard deviation is 11.871 and the average learning achievement of the control class is 59.14, the standard deviation is 11.107, the fourth hypothesis is obtained the significance value of applying the PBL (X) model of 0.001 < 0.05 and the calculated value of 3.987 > table of 1.720, critical thinking significance value (Y1) of 0.000<0.05 and calculated value of 8.337>table of 1.720, and learning achievement significance value (Y2) of 0.000 < 0.05 and calculated value of 8.337 > table of 1.720. then it can be concluded that the PBL learning model on critical thinking skills and mathematics learning achievement differs.